Digital microscope-assisted photography improves the accuracy of mosquito wing measurement - Zulzahrin, Zulhisham (Elsevier, 2024)
Wing measurement is an important parameter in many entomological studies. However, the methods of measuring wings vary with studies, and a gold standard method was not available for this procedure. This in turn limits researchers from confidently comparing their research findings with published data collected by other means of measurement. This study investigated the interchangeability of three commonly available methods for wing measurement, namely the calliper method, stereomicroscope-assisted photography method, and digital microscope-assisted photography method, using the laboratory colony of Aedes aegypti. It was found that the calliper method and the photography-based methods yielded similar results, hence the good interchangeability of these methods. Nevertheless, the digital microscope-assisted photography method yielded more accurate measurements, due to the higher resolution of the captured photos, and minimal technical bias during the data collection, as compared to the calliper-based and stereomicroscope-assisted photography methods. This study served as a reference for researchers to select the most suitable measurement method in future studies.